Acrometastasis of Squamous Cell Carcinoma of the Esophagus: Case Report - Freitas de Figueiredo Dias, Levindo Tadeu (2014)
Introduction: Acrometastasis to the hands is rare, accounting for approximately 0.1% of all metastatic osseous involvement and more exceptionally from gastrointestinal system tumors, as the esophageal carcinoma. Objective: To report a case of atypical squamous esophageal cancer cells with acrometastasis to the hand. Case report: Male, 48 years old, with clinical progressive dysphagia. He was submitted to endoscopy, which revealed an ulcerated lesion with elevated borders, measuring approximately 12 mm of diameter. Biopsy confirmed poorly differentiated carcinoma and invasive squamous cell, Grade III. It was performed esophagectomy after neoadjuvant radiotherapy and chemotherapy. After two years of surgery, patient developed edema, mild erythema and local pain in the left wrist and hand, restricting movements of the first and third fingers. His radiography showed extensive osteolytic lesions, bone scintigraphy with increased bone activity. A local biopsy confirmed metastatic squamous cell carcinoma of the soft tissue, the primary focus of the esophagus. Conclusion: Bone metastasis to extremity in esophageal carcinoma is rare. With increasing longevity of cancer, new propaedeutic must be discussed in the early detection of bone metastases.